New mouse model based on adenocarcinoma 4T1 cells expressing HPV16 E6 and E7 applied to assess the efficacy of therapeutic and prophylactic E6/E7-based HPV16 vaccines - Juris Jansons; Daria Avdoshina; Alesja Dudorova; Elena Royo Rubio; Liba Sokolovska; Dmitry Perminov; Ilze Lindenberga; Hannes Nicolai; Svetlana Gebrila; Sona Chowdhury; Dace Skrastina; Jurijs Nazarovs; et al. (Infectious Agents and Cancer)
Abstract Background Development of immunotherapies and vaccines to treat HPV16-associated cancer requires reliable/effective small animal models. We developed such a model based on the murine mammary gland adenocarcinoma cells engineered to express HPV16 oncoproteins E6 and E7, and used it to assess the protective and therapeutic potential of E6/E7-based DNA-immunogens. Methods 4T1luc2 subclones with single genomic inserts of HPV16 E6/E7 DNA (B2, H6) were obtained by lentiviral transduction. DNA-immunogens were designed encoding expression-optimized consensus HPV16 E6 and E7 mutated to disrupt p53- and Rb-binding, both controlled by the human elongation factor 1a promoter. In prophylactic settings, BALB/c mice received E6, E7, E6/E7 DNA or vector, followed by challenge with B2 or H6 cells, and in therapeutic settings, were challenged with B2 or H6 cells, and DNA-immunized with E6 or vector. In reference series, C57bl/6 mice were challenged with TC1/luc2 cells and DNA-immunized with E6, E7, or E6/E7, or vector DNA. Tumor growth was monitored morphometrically and by in vivo bioluminescence imaging (BLI); metastatic activity, by ex vivo organ BLI, PCR and histology, and in vitro cytokine production by T-cells of immunized mice, by flow cytometry. Results E6/E7-expressing 4T1luc2 subclones B2 and H6 longitudinally expressed mRNA of E7 and of E6*I, E6*II, full length E6 (E6FL) isoforms. The levels of expression of E6 and E7 mRNA significantly increased with time. In naïve mice, B2 and H6 generated solid tumors with lung metastases. B2 and H6 cells were used to assess the efficacy of prophylactic DNA-immunization with E6 and E7. In immunogenicity tests, E6 DNA recipients developed Th1-type T-cell response, their unstimulated T-cells produced IFN-γ and IL-2. E7 DNA was nonimmunogenic, while unstimulated T-cells produced TNF-α. In prophylactic settings, DNA-immunization with E6 and E7 suppressed formation of B2/H6 tumors. In therapeutic settings, DNA-immunization with E6 (not E7) restricted growth of TC-1/luc2 tumors, but had no effect on tumorigenic or metastatic activity of E6/E7-expressing 4T1luc2 cells. In both TC-1/luc2 and 4T1luc2E6/E7-models, E7 DNA recipients developed systemic inflammation manifested by enhanced formation of microgranulomas in the liver. Conclusions 4T1luc2 cells stably expressing HPV16 E6/E7 present an attractive alternative to TC-1 model allowing stringent assessment of both protective and therapeutic potential of E6/E7-based vaccines in BALB/c mice.